Influence of seed size and seed rate on seed yield of forage oats (Avena sativa) - KUMAR, DINESH; SETH, RAKESH; GANGAIAH, B (The Indian Journal of Agricultural Sciences, 2011)
A field experiment was conducted during 1997-98 to 1999-2000 at Jhansi , to study the effect of different seed size and seed rates on seed yield and its attributes in 2 varieties of oat (Avena sativa L.). ’JHO 822’ recorded significantly higher field emergence, seed yield (3 tonnes/ha) and its attributes than ’UPO 212’ (2.51 tonnes/ha). At par seed yields of 2.85, 2.66 and 2.75 tonnes/ha, respectively were observed across all the 3 seed rates of60, 80 and 100 kg/ha. Seed size did not have a significant impact on seed yield and its attributes in forage oats.